형질전환 소 난자의 동결보존기술 개발 - 엄상준; 양정석; 이수민; 조소영; 임준교; 허영태; 허영남; 구본철; 정기수; 김광재; 김지태; 김남형; et al. (Journal of animal reproduction & biotechnology (Online), 2013)
The purpose of this study is to improve production efficiency of vitrified-thawed transgenic bovine embryos. Transgenic bovine embryos were produced by injection of FIV-GFP lentiviral vector into perivitelline space of in vitro matured MІІ stage oocytes, and then in vitro fertilization. EGFP-expressing transgenic bovine blastocysts were cultured in serum-containing and serum–free medium. These blsatocysts were vitrified by pull and cut (PNC) container made with 0.25 cm plastic straw. Results indicate that total developmental rates of normal IVF embryo cultured in serumcontaining and–free medium into blastocyst were not significantly different (22.3 vs 21.5%) and those of GFPexpressing transgenic bovine embryo into blastocyst showed no significant difference between serum-containing (13.9%) and–free medium (13.1%). However, developmental rate of GFP transgenic embryo was significantly (P<0.05)lower than its of normal IVF embryos. In additional study, we vitrified GFP transgenic normal bovine blastocysts using PNC vitrification method. Survival rate of vitrified-thawed GFP transgenic blastocyst (23.1%) was significantly (P<0.05) lower than its of normal blastocysts (68.9%). Although, survival rate of vitrified-thawed GFP transgenic blastocyst was lower than its of normal blastocyst, our result may suggested that PNC vitrification method is feasible to cryopreserve transgenic embryos. Our next plan will be the production of GFP express transgenic bovine derived from vitrified-thawed embryos using PNC method. KCI Citation Count: 0